Feasibility Study In The Aspect Of Ecotourism Destination Products, In Puncak Village, Cigugur District, Kuningan Regency - Tina Wiryawati; Sapto Supriyanto; Haniek Listyorini (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Since 2016 the District Government declared "Kuningan as a conservation district", but despite the declaration as a conservation district, the development of tourism businesses tends to be far from conservation values. One of the villages that wants to maintain conservation values is Puncak Village, Cigugur Sub-district on the slopes of Mount Ceremei, by becoming an ecotourism destination. This research aims to conduct a feasibility study of Puncak Village as an ecotourism destination by assessing the condition of product feasibility both in the elements of tourist attraction, amenity feasibility and accessibility feasibility as an ecotourism destination. This feasibility study was pursued with an interactive qualitative method with in-depth interviews with informants, direct observation and collecting a number of data and documents. The result of the study state that the elements of the Puncak Village tourist attraction have fulfilled high feasibility criteria. A number of potential tourist attractions have been charged with ecotourism, namely adventure tourism, agrotourism, cultural tourism, educational tourism, and MSME tourism, which support the occurrence of ecotourism values in nature conservation, cultural conservation, learning and community empowerment. In the amenity element, Puncak Village has amenity criteria that are in accordance with ecotourism, both basic amenity, complementary amenity, and supporting amenity with a community empowerment model. In the accessibility element, it has a fairly good feasibility condition, well-paved village roads, and the road to the core zone is a path with very limited access. Ecotourism activities focus on jungle, special, utilization, religious, cultural and historical zones.